Posttranslational regulation of FOXA1 by Polycomb and BUB3/USP7 deubiquitin complex in prostate cancer - Park, Su H. (Sci Adv, 2021)
Forkhead box protein A1 (FOXA1) is essential for androgen-dependent prostate cancer (PCa) growth. However, how FOXA1 levels are regulated remains elusive and its therapeutic targeting proven challenging. Here, we report FOXA1 as a nonhistone substrate of enhancer of zeste homolog 2 (EZH2), which methylates FOXA1 at lysine-295. This methylation is recognized by WD40 repeat protein BUB3, which subsequently recruits ubiquitin-specific protease 7 (USP7) to remove ubiquitination and enhance FOXA1 protein stability. They functionally converge in regulating cell cycle genes and promoting PCa growth. FOXA1 is a major therapeutic target of the inhibitors of EZH2 methyltransferase activities in PCa. FOXA1-driven PCa growth can be effectively mitigated by EZH2 enzymatic inhibitors, either alone or in combination with USP7 inhibitors. Together, our study reports EZH2-catalyzed methylation as a key mechanism to FOXA1 protein stability, which may be leveraged to enhance therapeutic targeting of PCa using enzymatic EZH2 inhibitors.